'This is because … ': Authorial practice of (un)attending this in academic prose across disciplines. Issue 2 (3rd April 2018) - Jiang, Feng (Kevin); Wang, Feng
Abstract : While the tension between stylistic prescriptions and authorial practice in academic writing has attracted much attention in recent years, one common feature which is less fully explored is whether to attend demonstrative this (as in ' this uncertainty is because … ') or to leave this unattended (as in ' this is because … '). Based on a corpus of 160 research articles from eight disciplines, this study explores the authorial practice of this rhetorical choice, revealing how academic writers manage it to organize their arguments and persuade peers of their claims. In contrast to the style guides which recommend avoidance of unattended this, our data show that 35% of demonstrative this were unattended for rhetorical purposes in different knowledge fields. We also discuss differences in how writers in different disciplines favour diverse attending nouns to encapsulate the particular aspect of information their readers are likely to find most familiar, plausible and persuasive. We conclude that (un)attended this is a key feature in academic author's interactional resources, allowing them to build interaction with readers and claim credit for their ideas.